Enhancing Sustainable Performance in Hotel Industry: Supplier Innovativeness and Supply Chain Integration - Muthia Roza Linda; Vera Pujani; Syafrizal Syafrizal; Ma'ruf; Salut Muhidin (Jurnal Optimasi Sistem Industri, 2025)
The hotel industry relies on supply chain to deliver value added products and services, therefore selecting suppliers significantly affects the company's competitiveness in the market to improve sustainability performance. This research is important to determine how supplier innovativeness can improve sustainable performance. It provides a new contribution in assessing the influence of supplier innovativeness and supply chain integration on sustainable performance in the hotel industry, however their combined impact remains underexplored. The study examines the effect of supplier innovativeness on sustainable performance by focusing on the mediating role of supply chain integration in the hotel industry. The study employed a non-probability sampling method using a purposive sampling technique. The sample was selected based on the criterion that respondents held managerial or equivalent positions, as they were responsible for decision-making in hotel operations. A total of 111 respondents participated in the study and the hypotheses were analysed using SmartPLS software. Supplier innovativeness has a significant effect on supply chain integration and also contributes significantly to the improvement of sustainable performance. Indirectly, supplier innovativeness also significantly impacts sustainable performance through supply chain integration. Supply chain integration partially mediates the relationship between supplier innovativeness and sustainable performance. Emphasizing these factors can help hotels to achieve their sustainability goals, offering valuable insights for managers and policymakers. Hotel managers should actively engage in partnerships with innovative suppliers and invest in strengthening integration across their supply chains. This research contributes to the growing body of literature on sustainable supply chain management, particularly within the hospitality industry.